Marketing Channel Planning Analysis and Recommendations for Anshan Nanguo Pears - Pu, Xuyan (Asia Pacific Economic and Management Review, 2025)
Food is the foundation of people’s livelihood, with nutrition being the primary concern. People focus on nourishing their bodies through diet, pursuing healthy lifestyles in both ingredient selection and cooking methods. Amid the current trend of consumption downgrading, local consumers increasingly emphasize cost-effectiveness, adopting a consumption philosophy of "spending wisely and buying appropriately." Anshan Nanguo Pears, renowned as the "queen of pears" in the fruit industry for their unique nutritional value, are the subject of this study. This paper aims to fully leverage the resource advantages of the Nanguo Pear industry, focusing on industrial development, cultivating market entities, promoting agglomeration, and building a distinctive brand.